Interactions between brain and spinal cord mediate value effects in nocebo hyperalgesia - Tinnermann, A.; Geuter, S.; Sprenger, C.; Finsterbusch, J.; Büchel, C. (Science (American Association for the Advancement of Science), 2017)
Value information about a drug, such as the price tag, can strongly affect its therapeutic effect. We discovered that value information influences adverse treatment outcomes in humans even in the absence of an active substance. Labeling an inert treatment as expensive medication led to stronger nocebo hyperalgesia than labeling it as cheap medication. This effect was mediated by neural interactions between cortex, brainstem, and spinal cord. In particular, activity in the prefrontal cortex mediated the effect of value on nocebo hyperalgesia. Value furthermore modulated coupling between prefrontal areas, brainstem, and spinal cord, which might represent a flexible mechanism through which higher-cognitive representations, such as value, can modulate early pain processing.